The Application of Blended Teaching Model in College English Oral Courses in the Post Epidemic Era - Zhai, Jingwei (Journal of Theory and Practice of Contemporary Education, 2023)
English is the universal language of the world and an effective tool for us to communicate with others and understand the world. Having good oral English skills can help us better understand and learn advanced cultures and knowledge from other countries, and contribute to personal success and social development. Therefore, it is necessary to strengthen the ability of English oral teaching. The commonly used blended teaching mode is a very effective teaching method, and it must be firmly promoted and continuously improved. Therefore, this article will explore the problems in English oral teaching in the post pandemic era and the practical application of blended teaching mode.